R wave identification of blasting seismic waves in propagation process and its engineering application. Issue 4 (October 2021) - Yang, Zhaowei; Hu, Yingguo; Liu, Meishan; Yao, Erlei; Zhao, Gen; Wu, Xinxia
Abstract: The identification of R wave is helpful to analyze damage characteristics and damage analysis of nearby building caused by blasting seismic waves. According to the characteristics of low frequency, low speed and strong amplitude of R wave, a time-frequency filter for R-wave recognition is constructed and a R-wave recognition method based on S-transform is proposed. Firstly, the measured blasting vibration signal is transformed from time-space to time-frequency domain by S-transform. Secondly, according to the characteristics of R-wave, the R-wave filter is constructed and processed in time-frequency domain. Finally, the obtained R-wave signal in time-frequency domain is transformed into time-space signal by inverse transform. The results of numerical simulation and field measurement show that the R-wave identification method based on S-transform can effectively suppress and extract R-wave without destroying low-frequency body wave signal.